Global distribution of zoonotic digenetic trematodes: a scoping review - Yue Hu; Rong-Jian Zhan; Shi-Lin Lu; Yi-Yang Zhang; Min-Yu Zhou; Hui Huang; Ding-Ding Wang; Tao Zhang; Zi-Xin Huang; Yun-Fei Zhou; Zhi-Yue Lv (BMC, 2024)
Abstract Background Digenetic trematodes, including blood flukes, intestinal flukes, liver flukes, lung flukes, and pancreatic flukes, are highly diverse and distributed widely. They affect at least 200 million people worldwide, so better understanding of their global distribution and prevalence are crucial for controlling and preventing human trematodiosis. Hence, this scoping review aims to conduct a comprehensive investigation on the spatio-temporal distribution and epidemiology of some important zoonotic digenetic trematodes. Methods We conducted a scoping review by searching PubMed, Web of Science, Google Scholar, China National Knowledge Infrastructure, and Wanfang databases for articles, reviews, and case reports of zoonotic digenetic trematodes, without any restrictions on the year of publication. We followed the inclusion and exclusion criteria to identify relevant studies. And relevant information of the identified studies were collected and summarized. Results We identified a total of 470 articles that met the inclusion criteria and were included in the review finally. Our analysis revealed the prevalence and global distribution of species in Schistosoma, Echinostoma, Isthmiophora, Echinochasmus, Paragonimus, Opisthorchiidae, Fasciolidae, Heterophyidae, and Eurytrema. Although some flukes are distributed worldwide, developing countries in Asia and Africa are still the most prevalent areas. Furthermore, there were some overlaps between the distribution of zoonotic digenetic trematodes from the same genus, and the prevalence of some zoonotic digenetic trematodes was not entirely consistent with their global distribution. The temporal disparities in zoonotic digenetic trematodes may attribute to the environmental changes. The gaps in our knowledge of the epidemiology and control of zoonotic digenetic trematodes indicate the need for large cohort studies in most countries. Conclusions This review provides important insights into the prevalence and global distribution of some zoonotic digenetic trematodes, firstly reveals spatio-temporal disparities in these digenetic trematodes. Countries with higher prevalence rate could be potential sources of transmitting diseases to other areas and are threat for possible outbreaks in the future. Therefore, continued global efforts to control and prevent human trematodiosis, and more international collaborations are necessary in the future. Graphical Abstract